Study of 2D and 3D Methods for Worn Surface Analysis of Tool Materials - Hatos, I.; Hargitai, H.; Solecki, L. (Acta Technica Jaurinensis, 2015)
This paper is dealing with the comparison of the results given by different worn surface analysing methods. Maraging steel tool materials were used for the experiments. Specimens were produced by direct metal laser sintering from metal powder and by conventional way from rod having equivalent chemical content. The samples were age-hardened and surface treated by nitrocarburising and oxynitriding and they were tested by pin-on-disc type tribometer. The tribological behaviour was compared by using different methods for worn surface analysis.  Worn area of the surface was determined by the surface profiles of 2D measurements and the worn surface volume was calculated by using 3D images of focus variation microscopy measurements.